On Nuclear Terrorism - Levi, Michael (Harvard University Press, 2021)
"Nuclear terrorism is such a disturbing prospect that we shy away from its details. Yet as a consequence, we fail to understand how best to defeat it. Michael Levi takes us inside nuclear terrorism and behind the decisions a terrorist leader would be faced with in pursuing a nuclear plot. Along the way, Levi identifies the many obstacles, large and small, that such a terrorist scheme might encounter, allowing him to discover a host of ways that any plan might be foiled. Surveying the broad universe of plots and defenses, this accessible account shows how a wide-ranging defense that integrates the tools of weapon and materials security, law enforcement, intelligence, border controls, diplomacy, and the military can multiply, intensify, and compound the possibility that nuclear terrorists will fail. Levi draws from our long experience with terrorism and cautions us not to focus solely on the most harrowing yet most improbable threats. Nuclear terrorism shares much in common with other terrorist threats--and as a result, he argues, defeating it is impossible unless we put our entire counterterrorism and homeland security house in order. As long as we live in a nuclear age, no defense can completely eliminate nuclear terrorism. But this book reminds us that the right strategy can minimize the risks and shows us how to do it.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 21. Jun 2021)
Keywords: POLITICAL SCIENCE / Terrorism; National security -- United States; Nuclear terrorism -- United States -- Prevention; Nuclear weapons -- Government policy -- United States; Terrorism -- Government policy -- United States